Bypassing Parity Protected Cryptography using Laser Fault Injection in Cyber-Physical System - He, Wei (2016)
Lightweight cryptography has been widely utilized in resource constrained embedded devices of Cyber-Physical System (CPS) terminals. The hostile and unattended environment in many scenarios make those endpoints easy to be attacked by hardware based techniques. As a resourceefficient countermeasure against Fault Attacks, parity Concurrent Error Detection (CED) is preferably integrated with security-critical algorithm in CPS terminals. The parity bit changes if an odd number of faults occur during the cipher execution. In this paper, we analyze the effectiveness of fault detection of a parity CED protected cipher (PRESENT) using laser fault injection. The experimental results show that the laser perturbation to encryption can easily flip an even number of data bits, where the faults cannot be detected by parity. Due to the similarity of different parity structures, our attack can bypass almost all parity protections in block ciphers. Some suggestions are given to enhance the security of parity implementations.